Physico-chemical and catalytic properties of Fe-MKSF catalyst: Influence of MKSF clay as catalyst support - Hidayati Abdullah, Nur; Aida Zubir, Nor; Khairul Azam Selamat, Mohammad; Alrozi, Rasyidah; Nasuha, Norhaslinda; Imam Maarof, Hawaiah; Ballinger, Benjamin; Motuzas, Julius; C. Diniz da Costa, João (International Journal of Engineering and Technology, 2018)
The heterogeneous Fenton-like reaction is one of the most promising and effective treatment methods for the degradation of organic pollutants. In the present study, a detailed investigation on synthesis, characterization, and catalytic activity studies for oxidative degradation of methyl orange (MO) solution by iron oxide-immobilized montmorillonite KSF (Fe-MKSF) and pristine iron oxide catalysts were performed. The catalysts were synthesized via an impregnation-hydrothermal method using an autoclave reactor. Interestingly, the Fe-MKSF showed the highest catalytic removal of MO (85%) compared to the pristine iron oxides (30%) and MKSF (52%). This finding is well supported by the significant increase in surface area of the Fe-MKSF compared to the pristine catalysts (105.8 m2/g [Fe-MKSF] vs 52.2 m2/g [iron oxide] and 74.2 m2/g [MKSF]). The increased in surface area is favorable in having high accessibility of reactants towards the catalysts’ active sites which enable to diminish limitations in mass transfer during the reaction. These traits proved to be essential for the improved catalytic activity of the Fe-MKSF catalyst.